Mechanical bowel preparation prior to gynaecological laparoscopy enables better operative field visualization, lower pneumoperitoneum pressure and Trendelenburg angle during the surgery: a perspective that may add to patient safety - Üzeyir Kalkan; Murat Yassa; Kadir Bakay; Şafak Hatırnaz (IMR Press, 2021)
Background: To find the effects of mechanical bowel preparation (MBP) on operative field visualization, and to measure pneumoperitoneum pressure (PP) and Trendelenburg inclination angle (TIA) values. Methods: In this two-centred, randomised, single-blind and controlled study, 90 patients who underwent laparoscopic gynaecological surgery for benign conditions were included. After the exclusions, 44 patients received MBP with oral sodium phosphate enema (study group) and 42 did not receive bowel preparation or underwent diet restrictions (control group). An objective visual index, PP and TIA were measured in a stepwise design of assessments. Results: The Visual Index at first inspection right after establishing a 12 mmHg PP and a standard 30∘ TIA was found to be significantly in favour of the study group (p = 0.015). The lowest reached TIA in standard 12 mmHg PP following stepwise decrease was observed as 15.2∘ and 25∘ in the study and control groups, respectively (p < 0.001). The lowest reached PP was 8.9 mmHg and 11.9 mmHg in the study and control groups, respectively (p < 0.001). Patients who received MBP reported significantly higher levels of negative discomfort measures (p < 0.032), however 80% of those reported MBP as acceptable. Conclusion: Significantly better operative field visualization, lower TIA and PP was achieved with MBP. MBP enabled a decrement of either 10∘ in TIA or 3 mmHg in PP with an adequate operative field to proceed safely for the benign gynaecological laparoscopic operations in exchange for acceptable discomfort for the patients.